Factors Associated With Use of Telemedicine for Follow-Up of SLE in the COVID-19 Outbreak - So, Ho; Chow, Evelyn; Cheng, Isaac T.; Lau, Sze-Lok; Li, Tena K.; Szeto, Cheuk-Chun; Tam, Lai-Shan (Frontiers in Medicine, 2021)
Objective: To investigate the factors associated with telemedicine (TM) use for follow-up of SLE patients in the COVID-19 pandemic. Methods: This was a single-centered cross-sectional study conducted in Hong Kong. Consecutive patients followed up at the lupus nephritis clinic were contacted for their preference in changing the coming consultation to TM in the form of videoconferencing. The demographic, socioeconomic and disease data of the first 140 patients opted for TM and 140 control patients preferred to continue standard in-person follow-up were compared. Results: The mean age of all the participants was 45.6±11.8 years and the disease duration was 15.0±9.2 years. The majority of them were on prednisolone (90.0%) and immunosuppressants (67.1%). The mean SLEDAI-2k was 3.4±2.4, physician global assessment (PGA) was 0.46±0.62 and SLICC damage index was 0.97±1.23. A significant proportion of the patients (72.1%) had one or more comorbidities. It was found that patients with higher mean PGA (TM: 0.54±0.63 vs control: 0.38±0.59, p=0.025) and family monthly income > USD3, 800 (TM: 36.4% vs control: 23.6%; p=0.028) preferred TM, while full-time employees (TM: 40.0% vs control: 50.7%; p=0.041) preferred in-person follow-up. These predictors remained significant in the multivariate analysis after adjusting for age and gender. No other clinical factors were found to be associated with the preference of TM follow-up. Conclusion: When choosing the mode of care delivery between TM and physical clinic visit for patients with SLE, the physician-assessed disease activity as well as patient’s socio-economic status appeared to be important.